Quitting Behaviors Among Dual Cigarette and E-Cigarette Users and Cigarette Smokers Enrolled in the Tobacco User Adult Cohort. Issue 3 (20th October 2018) - Sweet, Laura; Brasky, Theodore M; Cooper, Sarah; Doogan, Nathan; Hinton, Alice; Klein, Elizabeth G; Nagaraja, Haikady; Quisenberry, Amanda; Xi, Wenna; Wewers, Mary Ellen
Abstract: Purpose: We examined quitting behaviors among a cohort of dual users (cigarettes and electronic cigarettes [e-cigarettes]) and exclusive cigarette smokers for: (1) cigarette smoking reduction, (2) quit attempts, (3) abstinence from cigarettes, and (4) abstinence from all tobacco products. Methods: Participants enrolled in the Tobacco User Adult Cohort and categorized as "daily" user of cigarettes and "daily" or "some days per week" use of e-cigarettes (ie, dual users; n = 88) or "daily" user of cigarettes only (ie, cigarette smokers; n = 617) served as the analytic sample. Participants were interviewed face to face every 6 months, through 18 months. Data on self-reported current product(s) used, cessation interest, quit attempts and abstinence from cigarettes, and all tobacco products were collected. Results: No difference in reduction of cigarette consumption over time was noted between groups. Rates of reporting an attempt to quit all tobacco products (≥ 24 hours of not using any tobacco in an attempt to quit) also did not differ by group. Compared to cigarette smokers, dual users were more likely to report abstinence from cigarettes at 6 months (OR = 2.54, p = .045) but not at 12 or 18 months. There was no significant difference in abstinence from all tobacco products by group at 6, 12, or 18 months. Conclusions: Although dual use of e-cigarettes has been cited as a potential cessation tool for cigarette smokers, our findings indicated that this association was only observed in the short term. We also found no evidence of any association between dual use and eventual abstinence from all tobacco products. Implications: Our study observed that, in the natural environment, dual users of cigarettes and e-cigarettes were more likely than cigarette smokers to quit cigarettes in the short term but no more likely to quit using cigarettes and all tobacco products over time.